Hadith #5519 - Sahih Muslim - Sayyar bin al-Ma'roor (Sahih Muslim)
I was walking with Thibit al-Bunani that he happened to pass by children and he greeted them. And Thibit reported that he walked with Anas and he happened to pass by children and he greeted them. and Anas reported that he walked with Allah’s Apostle (may peace be upon. him) and he happened, to pass by children and he greeted them.
Grade: Sahih